Evaluation of bioactive properties and phenolic compounds in different extracts prepared from Salvia officinalis L. - Martins, Natália (2015)
The therapeutic benefits of medicinal plants are well known. Nevertheless, essential oils have been the main focus of antioxidant and antimicrobial studies, remaining scarce the reports with hydrophilic extracts. Thus, the antioxidant and antifungal activities of aqueous (prepared by infusion and decoction) and methanol/water (80:20, v/v) extracts of sage (Salvia officinalis L.) were evaluated and characterized in terms of phenolic compounds. Decoction and methanol/water extract gave the most pronounced antioxidant and antifungal properties, being positively related with their phenolic composition. The highest concentration of phenolic compounds was observed in the decoction, followed by methanol/water extract and infusion. Fungicidal and/or fungi static effects proved to be dependent on the extracts concentration. Overall, the incorporation of sage decoction in the daily diet or its use as a complement for antifungal therapies, could provide considerable benefits, also being an alternative to sage essential oils that can display some toxic effects.